2019
DOI: 10.3390/catal9080685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transition Metal Additives on the Catalytic Performance of Cu–Mn/SAPO-34 for Selective Catalytic Reduction of NO with NH3 at Low Temperature

Abstract: The adsorption of NO, NH 3 , H 2 O, and SO 2 gaseous molecules on different transition metal oxides was studied based on density function theory (DFT), and three better-performing transition metal elements (Fe, Co, and Ce) were selected. Cu-Mn/SAPO-34 catalysts were prepared by impregnation method and then modified by the selected transition metals (Fe, Co, and Ce); the SO 2 resistance experiments and characterizations including Brunner−Emmet−Teller (BET), X-ray Diffraction (XRD), Scanning Electronic Microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
1
2
0
Order By: Relevance
“… 83 , 84 Jin et al 81 found that doped Ce was beneficial for reducing thermal stability of NH 4 HSO 4 on the catalyst surface, as shown in Figure 11 . This is also confirmed by Liu et al, 82 who prepared a Ce-Cu-Mn/SAPO-34 catalyst. Moreover, the Ce protects the main active components from being sulfurized, as shown in Figure 12 .…”
Section: The Optimization Of Mn-based Catalystsupporting
confidence: 82%
See 2 more Smart Citations
“… 83 , 84 Jin et al 81 found that doped Ce was beneficial for reducing thermal stability of NH 4 HSO 4 on the catalyst surface, as shown in Figure 11 . This is also confirmed by Liu et al, 82 who prepared a Ce-Cu-Mn/SAPO-34 catalyst. Moreover, the Ce protects the main active components from being sulfurized, as shown in Figure 12 .…”
Section: The Optimization Of Mn-based Catalystsupporting
confidence: 82%
“…Mn-based supported catalysts have made some progress. High redox performance, low surface area loss, and excellent acidity can be obtained with the combination of metal modification and support, thus improving the SO 2 and H 2 O resistance of the catalyst. ,,,, The metal oxide, the molecular sieve supports, and the carbon-based supports summarized in the previous section are mainly contained in the carrier. Among metal oxide supports, the TiO 2 is widely used, while the molecular sieve and carbon-based ones have a wide variety and flexible choices.…”
Section: The Optimization Of Mn-based Catalystmentioning
confidence: 99%
See 1 more Smart Citation